First-Time Users of ADHD Medication Among Children and Adolescents in Germany: An Evaluation of Adherence to Prescribing Guidelines Based on Claims Data - Scholle, Oliver; Kollhorst, Bianca; Riedel, Oliver; Bachmann, Christian J. (Frontiers in Psychiatry, 2021)
Background: Drug utilization studies based on real-world data are vital for the identification of potentially needed improvements to rational prescribing. This is particularly important for the pharmacological treatment of children and adolescents with attention-deficit hyperactivity disorder (ADHD) due to the associated potential side effects and the frequent use. Whereas prevalent use is well characterized, studies on first-time use of ADHD medication are scarce. This study aimed to evaluate off-label prescribing in first-time users of ADHD medication among children and adolescents in Germany based on three criteria: (i) lack of a documented ADHD diagnosis; (ii) first-time pharmacological treatment with a second-line drug; and (iii) patient age below six years. Methods: Based on German claims data, we included children and adolescents aged 0–17 years with a first-time dispensation of any ADHD medication in the period 2015–2017. These first-time users were characterized with regard to sex, age, specialty of the prescribing physician, documentation of an ADHD diagnosis, psychiatric hospitalization, psychiatric comorbidities, and history of other psychopharmacological drugs at first-time use. Results: The study population comprised 18,703 pediatric first-time users of ADHD medication. Of these, 9.8% had no documented ADHD diagnosis. Most of the ADHD drug users received first-line ADHD pharmacotherapy (methylphenidate, atomoxetine), whereas 2.6% were prescribed second-line ADHD medication (lisdexamfetamine, guanfacine, dexamfetamine, multiple ADHD drugs) as first drug. Overall, 1.2% of first-time users were aged below six years. A total of 12.7% of the study population met any off-label criterion. Conclusions: About 13% of pediatric first-time users of ADHD medication in Germany received an off-label pharmacotherapy at first-time use. Prescribing ADHD medication without a confirmed ADHD diagnosis was the most common of the three assessed off-label criteria. Off-label prescribing regarding drug choice and age of patients only occurred in a small percentage of initial pharmacological ADHD treatment. Our results suggest the need for improvement in rational prescribing, especially with regard to diagnostic requirements.